2014
DOI: 10.1007/s00417-014-2666-7
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of fluctuations of intraocular pressure after cataract surgery in primary angle closure glaucoma patients

Abstract: Cataract surgery decreased IOP fluctuations during the nocturnal period in PACG patients. These effects might partly prevent the progression of PACG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…A recent study investigated the effect of cataract surgery on the circadian IOP pattern in primary angle closure glaucoma patients using the contact lens sensor known as Triggerfish ® (Sensimed, Lausanne, Switzerland). [23] This study demonstrated that the mean range of IOP fluctuations during the nocturnal period was significantly decreased after cataract surgery although 24-h IOP fluctuation was not significantly changed. The nocturnal IOP reduction after surgery may be explained by our findings of the greater IOP-reducing effects in recumbent postures.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A recent study investigated the effect of cataract surgery on the circadian IOP pattern in primary angle closure glaucoma patients using the contact lens sensor known as Triggerfish ® (Sensimed, Lausanne, Switzerland). [23] This study demonstrated that the mean range of IOP fluctuations during the nocturnal period was significantly decreased after cataract surgery although 24-h IOP fluctuation was not significantly changed. The nocturnal IOP reduction after surgery may be explained by our findings of the greater IOP-reducing effects in recumbent postures.…”
Section: Discussionmentioning
confidence: 84%
“…[78910111213] Recent studies also demonstrated that phacoemulsification decreased diurnal IOP fluctuations in patients with pseudoexfoliation syndrome with open or occludable angles and decreased nocturnal IOP fluctuation in patients with primary angle closure. [2223] However, such IOP reductions may not always occur after phacoemulsification, and cataract surgery may even raise IOP postoperatively. [824] In the present study, we found that IOP was reduced (from 13.8 ± 1.9 mmHg to 12.6 ± 2.1 mmHg) after phacoemulsification when measured by GAT in the sitting position ( P = 0.007).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the decrease in IOP fluctuations during nocturnal period after cataract surgery using a contact lens sensor (CLS) in PACG patients was reported (Tojo et al. ). However, only relative changes of millivolt equivalent can be evaluated with a CLS that does not directly show the values of mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…Cataract surgery has in recent years been proposed as an IOP-lowering intervention in glaucoma patients. A recent study using the CLS suggested that it may produce a lowering of IOP fluctuations during the nocturnal period in patients with primary angle closure glaucoma [46]. Being able to visually demonstrate the individual response to these via the CLS output may contribute to improved patient understanding of glaucoma and adherence to treatment.…”
Section: Temporary Intraocular Pressure Monitoringmentioning
confidence: 99%